Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1365-8711.2000.03935.x
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of young radio-loud AGN

Abstract: This paper describes an investigation of the early evolution of extragalactic radio sources using samples of faint and bright Gigahertz Peaked Spectrum (GPS) and Compact Steep Spectrum (CSS) radio galaxies. Correlations found between their peak frequency, peak flux density and angular size provide strong evidence that synchrotron self absorption is the cause of the spectral turnovers, and indicate that young radio sources evolve in a self-similar way. In addition, the data seem to suggest that the sources are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
262
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(294 citation statements)
references
References 49 publications
29
262
3
Order By: Relevance
“…Thus, objects should evolve to lower radio power. However, it has been shown that very young compact radio sources will undergo a phase in which they increase in luminosity as they expand, because of the approximately constant density of the surrounding medium (Snellen et al 2000). GPS sources have similar optical luminosities to the FIR-luminous radio-excess galaxies (O'Dea et al 1996), but are much more powerful radio sources, placing them well into the FR II region of the diagram.…”
Section: Host Luminositiesmentioning
confidence: 99%
“…Thus, objects should evolve to lower radio power. However, it has been shown that very young compact radio sources will undergo a phase in which they increase in luminosity as they expand, because of the approximately constant density of the surrounding medium (Snellen et al 2000). GPS sources have similar optical luminosities to the FIR-luminous radio-excess galaxies (O'Dea et al 1996), but are much more powerful radio sources, placing them well into the FR II region of the diagram.…”
Section: Host Luminositiesmentioning
confidence: 99%
“…The observed turnover (or peak) frequencies (νo) of the CSS, MPS, GPS and HFP sources are νo < 0.5 GHz, νo < 1 GHz, 1 < νo < 5 GHz and νo > 5 GHz (O'Dea 1998;Dallacasa et al 2000;Coppejans et al 2015), respectively. These sources are believed to be young (rather than confined) AGN, some of which will likely evolve into FR I and FR II radio galaxies (Begelman 1996;O'Dea 1998;Snellen et al 2000;Conway 2002; De Vries et al 2002;Murgia et al 2002;Murgia 2003;Fanti 2009;An & Baan 2012;Orienti 2016). For the nearby (z ∼ 1) CSS, MPS, GPS and HFP sources, an empirical relation exists between the rest-frame turnover frequencies (νr, where νr = νo(1 + z)) and the linear sizes of the sources (O'Dea 1998; Snellen et al 2000;Orienti & Dallacasa 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As presented by Snellen et al, (2000) it is possible to set limits on the luminosity evolution of radio sources by exploiting the radio power -linear size (P-D) diagram as shown in Fig.2.8 (Snellen et al, 2000a).…”
Section: Css Gps and Hfpmentioning
confidence: 99%